2021
DOI: 10.1002/agj2.20711
|View full text |Cite
|
Sign up to set email alerts
|

Soil and plant growth response and trace elements accumulation in sweet corn and snow pea grown under fresh and carbonated coal fly ash amendment

Abstract: With the recent focus of using coal combustion residue fly ash in mineral carbonation for C capture, an end product, carbonated coal fly ash is generated. The physicochemical changes occur in fly ash during carbonation is hypothesized to improve its soil application potential compared to original fly ash. Therefore, in the present study, we tested carbonated coal fly ash against non‐carbonated (fresh) ash for its effect on soil, plant production, and elemental accumulation in plant parts. Plant pots of sweet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Premkumar et al (2017 reported that CFA is an effective stabiliser in enhancing the erosion resistance of dispersive soils. This industrial waste is also used in agriculture to improve soil properties and increase the yield of crops (Saidy et al 2020, Haris et al 2021, Ukwattage et al 2021.The presence of oxides, which neutralise acidic soils, and trace elements, that provide nutrients for…”
mentioning
confidence: 99%
“…Premkumar et al (2017 reported that CFA is an effective stabiliser in enhancing the erosion resistance of dispersive soils. This industrial waste is also used in agriculture to improve soil properties and increase the yield of crops (Saidy et al 2020, Haris et al 2021, Ukwattage et al 2021.The presence of oxides, which neutralise acidic soils, and trace elements, that provide nutrients for…”
mentioning
confidence: 99%